Tomographic analysis of midpalatal suture prior to rapid maxillary expansion - CHRISTOVAM,Ilana Oliveira (2021)
ABSTRACT Introduction: In Orthodontics and Facial Orthopedics, the timing of treatment onset may be critical and individual analysis should be applied to promote a favorable treatment planning. In this study, individual analysis of midpalatal suture (MS) and palatal measurements were performed in teenagers and young adult patients treated with rapid maxillary expansion (RME). Description: Twenty-six patients submitted to RME with a tooth-supported appliance (Hyrax) were evaluated. The inclusion criteria were: minimum age of 14 years, presenting all posterior teeth, diagnosed with transverse maxillary discrepancy, and with a clinical indication for maxillary expansion. The pretreatment CBCT scans of these patients were assessed to obtain the stages of MS maturation (MSM); density ratio (MSD); and palatal length, thickness (anterior, intermediate and posterior) and sagittal area. Results: The maturation stages present were C, D or E; the density ranged from 0.6 to 1, and lower density (MSD < 0.75) and higher density (MSD ≥ 0.75) groups were determined. Individuals with higher MSD presented smaller sagittal area, compared to the lower density group. Individuals in D and E MSM stages presented smaller sagittal area and intermediate thickness, compared to stage C. Conclusions: Smaller palatal sagittal area was observed in the high MSD groups and in the stages D and E of MSM.